Characterizing the genotypic and phenotypic diversity of Gardnerella vaginalis from vaginal clinical samples - Masete, Kopano Valerie (Division of Medical Virology, 2019)
Bacterial vaginosis (BV) is a common vaginal condition affecting reproductive-age women, especially in sub-Saharan Africa. With poor treatment outcomes, BV has been associated with pregnancy complications, pelvic inflammatory disease as well as acquisition and transmission of sexually transmitted diseases. While the etiology of BV is not well characterized, it is understood that Gardnerella vaginalis plays a critical role in BV by initiating the formation of the polymicrobial biofilm that characterizes BV and by degrading protective vaginal mucus through the release of sialidase. Recent evidence suggests that the G. vaginalis species is more heterogeneous that initially thought and that not all G. vaginalis may be involved BV. The aim of this study was thus to characterize the genotypic and phenotypic diversity of G. vaginalis isolates. This was achieved in vitro, using 109 G. vaginalis isolates that were previously purified from vaginal samples of 109 French women who were BV-positive (n = 75), BV-intermediate (n = 20) or BV-negative (n = 14), as diagnosed by Nugent scoring. To determine the genotypic diversity of G. vaginalis isolates, 90 isolates were successfully genotyped using their chaperonin-60 (cpn60) sequences, revealing the presence of four phylogenetic clades (subgroups A-D) made up of 13 subgroup A, 17 subgroup B, 58 subgroup C and 2 subgroup D isolates. To determine the phenotypic diversity of G. vaginalis isolates, sialidase activity, biofilm formation and susceptibility to antibiotics used to treat BV were measured. Sialidase activity was not detected in subgroup A and D isolates but was detected, at similar levels, in subgroup B and C isolates. Isolates from all subgroups of G. vaginalis could form similar amounts of biofilm. G. vaginalis isolates (n = 45) were largely resistant to metronidazole (71%), but sensitive to clindamycin (100%), moxifloxacin (91%) and augmentin (100%). The presence of prophages in G. vaginalis isolates was also investigated, revealing the presence of bacteriophage (phage)-like particles that could not be classified into any known phage families, whose phage status remains to be confirmed. In conclusion, G. vaginalis subgroup B and C isolates were the only ones that formed biofilm as well as had detectable sialidase activity suggesting that G. vaginalis subgroups B and C are most likely to be involved in BV. These results contribute to our knowledge of BV and could be useful in future studies that aim to design better treatment strategies for BV.